Penerapan model NHT melalui pendekatan saintifik untuk meningkatkan motivasi dan hasil belajar tematik siswa - Ro’sin Nadhiroh; Stefanus C. Relmasira; Tri Nur Ana Rahayu (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2019)
This study aims to improve students' motivation and thematic learning outcomes through the Numbered Heads Together (NHT) cooperative learning model through a scientific approach. This research is a classroom action research conducted in 2 cycles. The subjects of this study were the first grade students of Salatiga Elementary School 03 2017/2018 school year consisting of 28 students. Data collection using questionnaires and tests. Data analysis with comparative descriptive. Based on the results of the study that: Student learning motivation in the high category increased from 76% in cycle I, and increased again to 82% in cycle II. Learning outcomes in Indonesian language in the first cycle of 75% increased to 89% in the second cycle. PPKn content learning outcomes in the first cycle of 82% increased to 93% in the second cycle. Based on the results of these studies it can be concluded that this study was declared successful.